ANALISIS KAPASITAS PETANI DALAM USAHATANI BUAH NAGA DI DESA ALEBO JAYA KECAMATAN KONDA KABUPATEN KONAWE SELATAN - Opi, Saktiyani; Taufik, Yani; Rosmawaty, Rosmawaty (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2024)
The aim of this research was to; (1) Knowing and analyzing the capacity of farmers in dragon fruit farming in Alebo Jaya Village, Konda District, South Konawe Regency. This research was carried out in March-July 2024 with farmer informants. Determining the research location was carried out purposively with the consideration that farmers in Alebo Jaya Village, Konda District have been cultivating dragon fruit for a long time. This research used primary data and secondary data which were analyzed descriptively, using interview techniques with 10 dragon fruit farmers as informants. With the following results: This research shows that the capacity of farmers used in Alebo Jaya Village, Konda District, South Konawe Regency is the capacity of farmers related to eradicating the white fungus pest that attacks dragon fruit. Analysis of farmers' capacity in dragon fruit farming in Alebo Jaya Village, Konda District, South Konawe Regency. With the presence of white fungus medicine, farmers felt relieved and grateful because they were able to be helped in overcoming the problems they faced.